Stable Stratified Correlation and Linear Negative Correlation Between Serum Albumin and Risk of All-Cause Death in Patients with Ischaemic Stroke - Gaihong Xu; Juan Zhang (Artery Research)
Abstract Aims To assess the correlation between serum albumin and all-cause death in patients with ischaemic stroke. Methods In this prospective cohort study, a total of 1000 patients with ischemic stroke were included. Multivariate Cox regression analysis, subgroup analysis, receiver operating characteristic (ROC) curve, Kaplan–Meier survival analysis, and restricted cubic spline (RCS) plot were used to assess the association between serum albumin and all-cause death in patients with ischaemic stroke. Results A total of 272 patients with ischemic stroke died during a median follow-up of 25 months. Multivariate Cox regression analysis showed that the risk of all-cause death in patients with albumin at T2 (40–43 g/L) and T3 (>43 g/L) was 33.6% and 74.4% lower than that in patients with T1 (<40 g/L), respectively, and the risk of all-cause death decreased by 13.2% for every unit increase in albumin (P < 0.001). Subgroup analysis showed that the correlation between higher levels of albumin and lower risk of all-cause death was significant in all subgroups (P < 0.05). ROC analysis indicated that albumin could predict all-cause death in both the overall population and different sex groups (P < 0.001). Kaplan–Meier survival analysis revealed that with the extension of follow-up time, the higher the albumin, the slower the survival probability decreased (P < 0.001). RCS also established a linear negative correlation between albumin and the risk of all-cause death (P for nonlinearity = 0.092). Conclusion In patients with ischemic stroke, there was a stable stratified correlation and linear negative correlation between serum albumin and all-cause death risk.